Utilization of Suprathel® in delayed surgical management of toxic epidermal necrolysis (TEN): A case report - Isabella Lipkin; Michelle Hughes; W.B. Hughes (Burns Open)
Given the lack of established practice guidelines for the management of cutaneous symptoms associated with toxic epidermal necrolysis, treatments range from various dressings to skin substitutes. The following report details a case of a 21-year-old male patient with this diagnosis who presented nine days after rash eruption from an outside hospital with no signs of healing. The patient was then successfully managed surgically eleven days after symptom onset with debridement of epidermal blisters and placement of Suprathel®. To our knowledge, this publication is the first to describe the potential of this synthetic skin substitute in promoting epidermal regeneration for delayed surgical management of toxic epidermal necrolysis.